Randomised controlled trial of two sequential artemisinin-based combination therapy regimens to treat uncomplicated falciparum malaria in African children: a protocol to investigate safety, efficacy and adherence. Issue 3 (30th August 2017) - Schallig, Henk DFH; Tinto, Halidou; Sawa, Patrick; Kaur, Harparkash; Duparc, Stephan; Ishengoma, Deus S; Magnussen, Pascal; Alifrangis, Michael; Sutherland, Colin J
Abstract : Background: Management of uncomplicated Plasmodium falciparum malaria relies on artemisinin-based combination therapies (ACTs). These highly effective regimens have contributed to reductions in malaria morbidity and mortality. However, artemisinin resistance in Asia and changing parasite susceptibility to ACT in Africa have now been well documented. Strategies that retain current ACT as efficacious treatments are urgently needed. Methods: We present an open-label, randomised three-arm clinical trial protocol in three African settings representative of varying malaria epidemiology to investigate whether prolonged ACT-based regimens using currently available formulations can eliminate potentially resistant parasites. The protocol investigates whether a sequential course of two licensed ACT in 1080 children aged 6–120 months exhibits superior efficacy against acute P. falciparum malaria and non-inferior safety compared with standard single-course ACT given to 540 children. The primary endpoint is PCR-corrected clinical and parasitological response at day 42 or day 63 of follow-up. Persistence of PCR-detectable parasitaemia at day 3 is analysed as a key covariate. Secondary endpoints include gametocytaemia, occurrence of treatment-related adverse events in the double-ACT versus single-ACT arms, carriage of molecular markers of drug resistance, drug kinetics and patient adherence to treatment. Discussion: This protocol addresses efficacy and safety of sequential ACT regimens in P. falciparum malaria in Africa. The approach is designed to extend the useful life of this class of antimalarials with maximal impact and minimal delay, by deploying licensed medicines that could be swiftly implemented as sequential double ACT by National Malaria Control Programmes, before emerging drug resistance in Africa becomes a major threat to public health.